Sitting target - Jacobs, Alexander 1927-1979; Reed, Oliver 1938-1999; St. John, Jill 1940-; McShane, Ian 1942-; Woodward, Edward 1930-2009; Finlay, Frank 1926-2016 (2012)
"A killer has one more victim on his hit list - his faithless wife! Oliver Reed snarls and seethes his way through a brute-force '70s crime thriller in the tradition of Get Carter. Douglas Hickox, who would go on to helm such memorable films as 'Theatre of Blood' and 'Zulu Dawn', brings his filmmaking intensity to a story of revenge set in a London as bleak and brooding as the prison from which convicted killer Harry Lomart (Reed) and his fellow inmate (Ian McShane) escape. Once free, Harry sets out to exterminate his seductive wife (Jill St. John), who carries another man's child. Armed with a handgun and fueled by rage, Harry draws closer to his sitting target. Also closing in: a police inspector (Edward Woodward), who's determined to protect the hunted woman. Reed and McShane - one grim, one voluble, and both steeped in violence - make an intimidating tough-guy team."
Bildformat 1.85:1 (16:9)
Original 1972
Keywords: Revenge / Drama; Crime / Drama; Escaped prisoners / Drama; Crime; Escaped prisoners; Revenge; Feature films; Drama; Film; DVD-Video